Fatores indutores e supressores da eritropoiese em caninos doentes renais crônicos - Hermeto, Larissa Correa [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The articular cartilage is a tissue that has limited capacity for repair after an acute injury, and the efficacy of current treatments usually results in relief of symptoms, and not in regeneration of damaged tissue. Focusing on this issue, the aim of this work was to evaluate the effect of therapy with autologous mesenchymal stem cells (MSC) in the regeneration of rabbits articular cartilage submitted to experimental knee osteoarthritis. Twenty four adult New Zealand White rabbits were randomly divided into four groups: GC (control group); GPRP (platelet rich plasma group); GCTM (undifferentiated autologous mesenchymal stem cells group); GCTMdif (chondrocyte differentiated autologous mesenchymal stem cells group). All animals were osteoarthritis-induced by application of collagenase solution, and four weeks after induction, they received the specific treatments to each group. After sixty days of therapy, the animals were sacrificed and articular surfaces were submitted to macroscopic and histomorphological evaluations. At the same time were performed adipogenic, chondrogenic and osteogenic differentiation of MSC, characterizations through cytometric analysis, and evaluation of cytogenetic damage by the Comet Assay. The macroscopic and histomorphological examinations revealed a better repair tissue in the groups treated with MSC. Cytometric analyzes showed positive results for MSC immunostaining, and differentiation showed that MSC were able to differentiate into adipocytes, chondrocytes and osteoblasts. Through the Comet Assay, it was noticeable that the cytogenetic damage increased after the second passage of the MSC. It was concluded that there are beneficial effects of the combination of MSC derived from adipose tissue and platelet-rich plasma in the regeneration of articular cartilage in knees of rabbits undergoing experimental osteoarthritis, and there is no difference when MSC are used undifferentiated or differentiated into ...

A cartilagem articular é um tecido que possui capacidade limitada de reparo após uma lesão aguda, e a eficácia dos tratamentos atuais geralmente resulta em alívio dos sintomas, e não em regeneração do tecido lesado. Incidindo sobre esta problemática, o objetivo do presente trabalho, foi avaliar o efeito da terapia com células-tronco mesenquimais (CTM) autólogas na regeneração da cartilagem articular de joelhos de coelhos submetidos a osteoartrite experimental. Foram utilizados 24 coelhos da raça Nova Zelândia Branca, os quais foram divididos aleatoriamente em quatro grupos: GC (grupo controle); GPRP (grupo plasma rico em plaquetas); GCTM (grupo células-tronco mesenquimais autólogas indiferenciadas); GCTMdif (grupo células-tronco mesenquimais autólogas diferenciadas em condrócitos. Todos os animais foram induzidos a osteoartrite por meio da aplicação de solução de colagenase, e após quatro semanas receberam os tratamentos propostos para cada grupo. Após sessenta dias da terapia, os animais foram eutanasiados e as superfícies articulares foram submetidas a avaliações macroscópicas e histomorfológicas. Paralelamente foram realizadas diferenciações adipogênicas, condrogênicas e osteogênicas das CTM, caracterizações das mesmas por meio de análise citométrica, e avaliações de danos citogenéticos pelo Teste do Cometa. Os resultados dos exames macroscópicos e histomorfológicos revelaram um melhor tecido de reparação nos grupos tratados com CTM. As análises citométricas apresentaram resultados de imunomarcações positivos para CTM, e as diferenciações revelaram que as CTM foram capazes de se diferenciar em adipócitos, condrócitos e osteoblastos. Por meio do Teste do Cometa, foi possível notar que os danos citogenéticos aumentaram após a segunda passagem das CTM. Conclui-se que há efeitos benéficos da associação de CTM derivadas do tecido adiposo e plasma rico em plaquetas na regeneração ...
Keywords: Coelho; Medicina regenerativa; Cartilagem articular; Tecido adiposo; Células-Tronco; Joelhos; Articular cartilage